2019
DOI: 10.1080/21645515.2018.1564438
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for cross-protection but not type-replacement over the 11 years after human papillomavirus vaccine introduction

Abstract: Examination of cross-protection and type replacement after human papillomavirus (HPV) vaccine introduction is essential to guide vaccination recommendations and policies. The aims of this study were to examine trends in non-vaccine-type HPV: 1) genetically related to vaccine types (to assess for cross-protection) and 2) genetically unrelated to vaccine types (to assess for type replacement), among young women 13-26 years of age during the 11 years after HPV vaccine introduction. Participants were recruited fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 33 publications
1
30
1
Order By: Relevance
“…Several studies have evaluated the occurrence of HPV type replacement, using differing methodologies; comparison of the HPV prevalence between the postvaccination and prevaccination era, 8‐10 between vaccinated and unvaccinated persons in the postvaccination era 11 or via individually randomised HPV vaccination trials 12 . Importantly, a recent meta‐analysis of the above‐mentioned studies found an increasing trend in the pooled nonvaccine targeted (and noncross‐protected) HPV types, 13 further to an earlier meta‐analysis which found possible increases in HPV 39 and 52 14 …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have evaluated the occurrence of HPV type replacement, using differing methodologies; comparison of the HPV prevalence between the postvaccination and prevaccination era, 8‐10 between vaccinated and unvaccinated persons in the postvaccination era 11 or via individually randomised HPV vaccination trials 12 . Importantly, a recent meta‐analysis of the above‐mentioned studies found an increasing trend in the pooled nonvaccine targeted (and noncross‐protected) HPV types, 13 further to an earlier meta‐analysis which found possible increases in HPV 39 and 52 14 …”
Section: Introductionmentioning
confidence: 99%
“…However, type-specific trends of non-vaccine-type HPV are more heterogeneous without consistent signals of type replacement [ 26 ]. The likelihood of type replacement remains ambiguous, and further studies are needed to monitor for cross-protection and possible type replacement after the introduction of the HPV vaccine [ 23 , 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The vaccine offers cross protection to hpv types genetically related in the same species, so we consider the pentavalent vaccine essentially a bivalent vaccine and the 9-valent vaccine a 3-valent vaccine[8]…”
Section: Methodsmentioning
confidence: 99%
“…The authors do not discard the possibility of type replacement for non-vaccine HPV types not genetically related. [8]…”
Section: Introductionmentioning
confidence: 99%